Analisis Framing Berita Pemberhentian PSBB Surabaya Raya di Media Online kompas.com dan suarasurabaya.net - Ruri Handariastuti; Zainal Abidin Achmad; Airlangga Bramayudha (Jurnal Ilmu Komunikasi, 2020)
This research discusses the Analysis of the News Framing of PSBB Surabaya Raya Termination in Online Media Kompas.com and Suarasurabaya.net Edition 8-9 June 2020. This research uses constructive paradigm using Framing Pan and Kosicki analysis method with the assumption that each news article has a frame which functions as a center of the organizational idea. Kompas.com dan suarasurabaya.net have their own views to frame their news. Kompas.com is a national online media, while for suarasurabaya.net is a local online media that much people interest in Surabaya, especially for radio media. The result shows news article has used some of them have a lack point and suarasurabaya.net more construct East Java Governor figure.